DIGITAL BANKING ADOPTION, BANK SIZE, AND BANK PERFORMANCE IN INDONESIA - Setiawan, Rahmat; Prakoso, Leonardus (Jurnal Ekonomi dan Bisnis Airlangga, 2024)
Introduction: The adoption of technology has become prevalent in the banking sector. This research investigates the potential correlation between the implementation of digital banking adoption and the bank performance (Return on Assets and Operational Efficiency Rasio), while considering the factor of bank size. Methods: This research utilizes panel data regression to assess the effect of digital banking adoption on the performance of banking firms. Additionally, it explores whether the bank size influences the strength of the relationship between the independent and dependent variables. Results: Digital banking adoption (DBA) has a significant negative impacts Return on Assets (ROA) and has a significant positive effect on the Operational Efficiency Ratio (BOPO). The bank size weakens the negative impact of DBA on ROA; the bank size also weakens the positive impact of DBA on BOPO. Conclusion and suggestion: This study demonstrates the occurrence of the profitability paradox and economies of scale in Indonesian banking companies. For decision-makers in banking companies, these findings can be considered when determining the optimal company size to enhance digital banking adoption and improve banking performance.